La administracion ordinaria de bienes en la sociedad conyugal y el derecho constitucional de la equidad de genero en el Ecuador - Baquero Gallo, Greta Moraima (2013)
Through this research I aim to provide a technical and scientific contribution of the legal aspects inherent to the problem because in our country since 1970, begins a hard struggle by women for equal rights with men and specifically to equate in terms of administration and disposition of property of the conjugal partnership. The Constitution of the Republic of Ecuador in effect, guarantees equality between people and the enjoyment of the same rights, duties and opportunities, as well as the state guarantees its citizens equal rights in decision making for the management conjugal society and goods society. However, the current Ecuadorian Civil Code discriminates gender equity in relation to the ordinary administration of the conjugal partnership property. I think the law should leave at liberty to choose spouses, according to the interests that suits them, taking one of several forms referred to in the Andean legislation. It would be essential that it give both spouses the same powers for the duration of the marriage, ie a system of joint administration, necessarily requiring the express consent of both spouses for the most relevant administrative acts, and presuming the agreement in other acts when performed by only one of them, it's to ensure the protection of family assets.